Rapid green synthesis of gold nanoparticles: synthesis, characterization and antimicrobial activities : Rapid green synthesis of gold nanoparticles - Hatipoğlu, Abdulkerim (Progress in Nutrition, 2021)
In this research, an easy and environmentally friendly method was presented for the biosynthesis of gold nanoparticles (AuNPs) with Allium ampeloprasum (AA) leaf extract as a reducing and stabilizing agent. The maximum absorption peak was found to be around 535 nm with ultraviolet (UV)-visible spectrophotometer. When the Transmission Electron Microscopy (TEM), Emission Scanning Electron Microscopy (FE-SEM) and energy dispersive X-ray (EDX) analyzes were examined, it was seen that the crystal size of the synthesized AuNPs was between 6.02-17.36 nm and their shape was mostly spherical. The size of the crystal structures of AuNPs was calculated as 22.76 nm from the X-ray diffraction (XRD) analysis data. Fourier Transform Infrared (FT-IR) Spectroscopy results showed that phenolics, aromatic compounds and proteins were effective in the reduction and stabilization of AA-AuNPs. The average size of AuNPs was determined as 96.46 nm with Zetasizer. It was determined that AuNPs have a very strong inhibitory effect on pathogenic bacteria (Escherichia coli, Staphylococcus aureus, Bacillus subtillis and Pseudomonas aeruginosa) and Candida albicans by the minimum inhibitory concentration (MIC) method.